(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Indian IT industry is one of the major industries in India which has fostered growth and development of the economy by its enormous contribution towards GDP growth and employment generation .Besides providing skilled man power the country serves as a lucrative outsourcing destination for IT and IT enable services. The government has been longing towards growth and development of the sector and to further this objective it has administered several policy measures for its advancements. These developmental initiatives of the government are worth praise but a sincere effort towards analysing its efficacy is the need of the hour. The present study intends to apply statistical tools like Correlation, Regression, ANOVA, t test and Z test for analysing the effectiveness of the government initiatives in fostering growth and development of the sector.